Beyond static spatial management: Scientific and legal considerations for dynamic management in the high seas. (December 2020) - Ortuño Crespo, Guillermo; Mossop, Joanna; Dunn, Daniel; Gjerde, Kristina; Hazen, Elliott; Reygondeau, Gabriel; Warner, Robin; Tittensor, Derek; Halpin, Patrick
Abstract: Natural and human stressors in the high seas act across a wide range of spatial and temporal scales. These include direct interaction such as fisheries bycatch or indirect interaction like warming oceans and plastic ingestion. Area-based management tools (ABMTs), such as marine protected areas and time-area closures, are a widely accepted and a broadly successful form of management used to mitigate localized human impacts on marine species and ecosystems. Protection provides an opportunity for population recovery, which can then propagate outside of the closure. As the United Nations negotiates a new treaty on the conservation and sustainable use of biodiversity beyond national jurisdiction, efforts to design and implement high seas ABMTs at appropriate scales are critical to ensure that these spatial protection measures are most effective and climate-ready in the face of changing oceans. Here we identify the four most important temporal scales – contemporary, intra-annual, multi-annual and multidecadal – for aligning high seas ABMTs to relevant ecological, oceanographic and atmospheric processes. From this, we explore how managers and decision-makers can integrate this knowledge when implementing a new treaty.